2016
DOI: 10.21873/anticanres.11252
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Triweekly Nab-Paclitaxel Combined with S-1 in Patients with HER2-negative Metastatic Breast Cancer

Abstract: The response rate was 66.7%. The clinical benefit rate was 77.8%. Our study shows the efficacy and the feasibility of this combination therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…S-1 (Taiho Pharmaceutical Company), an oral combination of the fluoropyrimidine tegafur, the DPD inhibitor gimeracil, and oteracil potassium, intended to reduce gastrointestinal toxicity of fluorouracil, has shown efficacy in various gastrointestinal malignancies (3)(4)(5). Phase II studies of S-1 as first-line therapy for metastatic pancreatic cancer resulted in response rates of 21.1% to 37.5% (6).…”
Section: Introductionmentioning
confidence: 99%
“…S-1 (Taiho Pharmaceutical Company), an oral combination of the fluoropyrimidine tegafur, the DPD inhibitor gimeracil, and oteracil potassium, intended to reduce gastrointestinal toxicity of fluorouracil, has shown efficacy in various gastrointestinal malignancies (3)(4)(5). Phase II studies of S-1 as first-line therapy for metastatic pancreatic cancer resulted in response rates of 21.1% to 37.5% (6).…”
Section: Introductionmentioning
confidence: 99%
“…Several multiagent chemotherapy regimens have demonstrated modest survival benefits in the first line treatment (4). S-1 (5), an oral combination of the fluoropyrimidine tegafur, the DPD-inhibitor gimeracil, and oteracil potassium, intended to reduce gastrointestinal toxicity of fluorouracil, is commonly used in Asia for management of gastrointestinal malignancies including GC (6,7). A network meta-analysis reported that S-1 regimens were more effective than fluorouracil in advanced GC (8).…”
Section: Introductionmentioning
confidence: 99%